Why Do Labor Unions Advocate for Minimum Wage Increases? - Jeffrey Clemens; Michael R. Strain (Institute of Labor Economics (IZA), 2023)
Over the past decade, organized labor has played a significant role in advocating for minimum wage increases. Why might this be, given that the minimum wage may act as a substitute for the bargaining power offered by labor unions? In this paper, we study the interplay between minimum wages and union membership. We estimate that each dollar in minimum wage increase predicts a 5 percent increase (0.3 pp) in the union membership rate among individuals ages 16–40. Consistent with a classic "free-riding" hypothesis, however, we find that minimum wage increases predict declines in union membership among the minimum wage's most direct beneficiaries. Instead, increases in union membership occur among much broader groups that are not directly affected by the minimum wage.
Keywords: D71; D78; P16; 330; political economy; social choice; minimum wage; unionization